2023
DOI: 10.25165/j.ijabe.20231602.7424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray adjuvants and operation modes on droplet deposition and elm aphid control using an unmanned aerial vehicle

Abstract: A conventional spraying mode and a fully autonomous fruit tree operation mode using a model DJ T30 unmanned aerial vehicle (UAV) were used to control aphids control on elm trees and to clarify the distribution of droplets in elm trees sprayed by a UAV. The effects of six aviation spray adjuvants on elm canopy droplet deposition and aphid control were evaluated. ImageJ software was used to analyze and measure the droplet density and deposition of water sensitive paper in two modes; this was done to calculate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…The effect of different flight modes on the effective swath was analysed, and it can be found that when the UAV flew inter-row, whether it was unidirectional operation or reciprocating operation, the position of the effective swath was not uniform on either side of the UAV's route but was approximately 3 m to 4 m off the UAV's course in the downhill direction. The reason for this phenomenon is that when the UAV flew inter-row, unlike when it flew along the tops of the trees (Dou et al, 2023), some of the droplets sprayed by the UAV landed directly on the leaves of the fruit trees below the UAV, and the low planting density of the mountain orchards, influenced by the rotor airflow of the UAV (Zhang et al, 2023) and the natural wind on the mountain, led to a shift in the effective swath along the downhill direction. Therefore, to avoid the misspraying of fruit trees in the direction of the hill, the heavy spraying of fruit trees in the downhill direction, and spraying agents falling on nontarget crops, causing crop damage and environmental pollution, it is recommended to fly along the treetops when operating in the Nanguo pear orchard mountain settings.…”
Section: Droplet-size Spectrum and Position Of The Effective Swathmentioning
confidence: 99%
“…The effect of different flight modes on the effective swath was analysed, and it can be found that when the UAV flew inter-row, whether it was unidirectional operation or reciprocating operation, the position of the effective swath was not uniform on either side of the UAV's route but was approximately 3 m to 4 m off the UAV's course in the downhill direction. The reason for this phenomenon is that when the UAV flew inter-row, unlike when it flew along the tops of the trees (Dou et al, 2023), some of the droplets sprayed by the UAV landed directly on the leaves of the fruit trees below the UAV, and the low planting density of the mountain orchards, influenced by the rotor airflow of the UAV (Zhang et al, 2023) and the natural wind on the mountain, led to a shift in the effective swath along the downhill direction. Therefore, to avoid the misspraying of fruit trees in the direction of the hill, the heavy spraying of fruit trees in the downhill direction, and spraying agents falling on nontarget crops, causing crop damage and environmental pollution, it is recommended to fly along the treetops when operating in the Nanguo pear orchard mountain settings.…”
Section: Droplet-size Spectrum and Position Of The Effective Swathmentioning
confidence: 99%